A comparison of chloroplast genome sequences in Aconitum (Ranunculaceae): a traditional herbal medicinal genus - Hanghui Kong; Wanzhen Liu; Gang Yao; Wei Gong (PeerJ, 2017)
The herbal medicinal genus Aconitum L., belonging to the Ranunculaceae family, represents the earliest diverging lineage within the eudicots. It currently comprises of two subgenera, A. subgenus Lycoctonum and A. subg. Aconitum. The complete chloroplast (cp) genome sequences were characterized in three species: A. angustius, A. finetianum, and A. sinomontanum in subg. Lycoctonum and compared to other Aconitum species to clarify their phylogenetic relationship and provide molecular information for utilization of Aconitum species particularly in Eastern Asia. The length of the chloroplast genome sequences were 156,109 bp in A. angustius, 155,625 bp in A. finetianum and 157,215 bp in A. sinomontanum, with each species possessing 126 genes with 84 protein coding genes (PCGs). While genomic rearrangements were absent, structural variation was detected in the LSC/IR/SSC boundaries. Five pseudogenes were identified, among which Ψrps19 and Ψycf1 were in the LSC/IR/SSC boundaries, Ψrps16 and ΨinfA in the LSC region, and Ψycf15 in the IRb region. The nucleotide variability (Pi) of Aconitum was estimated to be 0.00549, with comparably higher variations in the LSC and SSC than the IR regions. Eight intergenic regions were revealed to be highly variable and a total of 58–62 simple sequence repeats (SSRs) were detected in all three species. More than 80% of SSRs were present in the LSC region. Altogether, 64.41% and 46.81% of SSRs are mononucleotides in subg. Lycoctonum and subg. Aconitum, respectively, while a higher percentage of di-, tri-, tetra-, and penta- SSRs were present in subg. Aconitum. Most species of subg. Aconitum in Eastern Asia were first used for phylogenetic analyses. The availability of the complete cp genome sequences of these species in subg. Lycoctonum will benefit future phylogenetic analyses and aid in germplasm utilization in Aconitum species.